Some Noteworthy Plants from Birbhum District. West Bengal - Basak, R. K. (Indian Forester, 1979)
The occurrence of eleven rare taxa in Birbhum district, West Bengal has been recorded with annotations. Rolala verticillaris Linn. is reported from the Eastern India for the first time.